ESBL-Producing Klebsiella pneumoniae in the Broiler Production Chain and the First Description of ST3128 - Daehre, Katrin; Projahn, Michaela; Friese, Anika; Semmler, Torsten; Guenther, Sebastian; Roesler, Uwe H. (Frontiers in Microbiology, 2018)
ESBL-producing Klebsiella pneumoniae (K. pneumoniae) represent an increasing problem both in human and veterinary medicine. As SHV-2 - encoding K. pneumoniae were recently detected in the broiler production we were interested in investigating a possible transmission along the broiler production chain and, furthermore, in evaluating their possible impact on human health. Therefore, forty-one ESBL-producing K. pneumoniae originating from a parent flock, from the hatcherys’ environment during the hatching of that parent flocks’ chickens, and from an associated fattening flock were investigated on an Illumina Miseq. Whole genome sequences were analyzed concerning their MLST-type, cgMLST-type, genotypic and phenotypic resistance, and plasmid profiles and virulence genes. Irrespective of the origin of isolation all investigated isolates were multi-drug resistant, harbored the same ESBL-gene blaSHV-2, shared the same sequence type (ST-3128ST3182) and displayed 100% similarity in core genome multilocus sequence typing (cgMLST). In addition, in silico plasmid typing found several Inc/Rep types associated with ESBL-plasmids. Summarizing, identical clones of SHV-2 - producing K. pneumoniae were detected in different stages of the industrial broiler production in one out of seven investigated broiler chains. This proves the possibility of pseudo-vertical transmission of multi-resistant human pathogens from parent flocks to hatcheries and fattening flocks. Furthermore, the importance of cross-contamination along the production chain was shown. Although the ESBL-producing K. pneumoniae clone detected here in the broiler production has not been associated with clinical settings so far, our findings present a potential public health threat.